Customer Loyalty and its Influence on Price Wars’ Intensity in the Indonesian Lighting Industry - Edwinarto, Dominicus; Arief, Muhtosim; Alamsjah, Firdaus; Heriyati, Pantri (International Journal of Engineering and Technology, 2018)
Several aspects of consumer behavior can increase the likelihood of price conflicts where organizations are subsequently influenced to engage in price wars. As the main aspect of business activities relates to the success of financial transactions, customer loyalty and price sensitivity becomes a decisive factor that defines market characteristics in the long run. Using quantitative survey data from respondents in the Indonesian lighting industry, this research is aimed to generate an understanding of how practitioners view their customer’s characteristics in relation to competitive interaction. The study found that within the context of competition, firms regard loyalty and sensitivity to be influenced by sufficient acceptance of price positioning strategies.